P046 More teaching, less sleeping: The impact of stressful periods of the school year on the sleep of Australian schoolteachers. (7th October 2021) - Friday, M; Gupta, C; Ferguson, S
Abstract: Introduction: There are approximately 270, 00 schoolteachers in Australia and this population experience multiple stressors at work. This can lead to poor sleep quality and quantity and, consequently, adverse outcomes for both schoolteachers and students. While it is well-established that certain periods of the year may lead to increased stress for schoolteachers, the impact of this on sleep is unknown. The current study aimed to investigate the effect of stressful periods of the school year on the sleep of schoolteachers. Methods: The Pittsburgh Sleep Quality Inventory (PSQI) and questions on stressful school periods (including report writing, standardised testing, school appraisal, and teacher performance) were completed online by 775 Australian primary and secondary schoolteachers (89.1% female, 29.9% 25–34 years). Pearson Chi-square analyses were performed. Results: Scores on the PSQI indicated that 611 (79.0%) of participants were experiencing poor sleep quality. There were significant relationships between each of the stressful periods of the year and PSQI score, such that increased stress during periods of report writing (p<0.001), standardised testing (p<0.001), school appraisal (p<0.001), and teacher performance (p<0.001) was associated with poor sleep quality. Discussion: Australian schoolteachers are at risk of poor sleep quality and quantity, and this is exacerbated by stressful periods of the school year. Given the vital role schoolteachers play in the community, organisations should be mindful of these periods of the year in order to improve the sleep of schoolteachers.